Investigating the effect of synbiotic supplementation on inflammatory indices in critically ill septic children: a protocol study for randomized control trial - Ali Chamani; Faezeh Mashhadi; Gholamreza Khademi; Mohsen Nematy; Maryam Emadzadeh; Majid Sezavar; Fatemeh Roudi (Trials)
Abstract Background Sepsis, a severe inflammatory response to infection, is a global health priority due to its high mortality and long-term disability rates. Its pathophysiology involves both inflammation and immune suppression. Managing sepsis requires significant healthcare resources and expenditure, with sepsis being a leading cause of hospital costs. Gut microbiotas play a crucial role in sepsis, and probiotics show promise in managing it by restoring microbial balance. Despite advances, targeted therapies for sepsis remain elusive, necessitating innovative approaches such as probiotic therapy. Method Fifty-four eligible patients with sepsis will be randomly assigned to either the synbiotic or placebo group. The synbiotic supplement, KidiLact, comprises ten probiotic strains and prebiotic fructooligosaccharides. Participants will receive two sachets daily for 7 days, mixed with sterile water and administered orally or via gavage. Inflammatory factors including interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) will be evaluated. Anthropometric measurements, nutritional assessment, biochemical analysis, and clinical evaluation will be conducted to assess treatment outcomes. Statistical analysis will be performed to compare results between the two groups, employing SPSS version 19 with a significance level of P < .05. Conclusion This randomized clinical trial aims to evaluate synbiotic supplementation effects on inflammatory markers and clinical outcomes in pediatric sepsis patients in the pediatric intensive care unit (PICU). Probiotics have shown promise in reducing proinflammatory cytokines like IL-6, TNF-α, and CRP, which are vital in the inflammatory response. Synbiotics can enhance gut integrity, preventing pathogen translocation and reducing inflammation. If our expectations regarding the effects of probiotics are correct, we can use them as a cost-effective supplement to improve the condition of pediatric sepsis in hospitals. Trial registration IRCT,IRCT20230523058266N1 Registered 30 October 2023, https://irct.behdasht.gov.ir/trial/71397 .